Analisis Kritis Permasalahan Pendidikan Islam Indonesia di Era Global - Musrifah Musrifah (UIN Walisongo Semarang, 2018)
The purpose of this study is to find out the problems of national education in Indonesia in a global context. This research method uses library research. The results showed that national education experienced problems including the first, the Philosophical Mistakes that interpreted the quality of education with the Achievement Index, second, Weakening the Empowerment of Educators (Teachers), Third Education Management was centralized, structuralistic, and bureaucratic, fourth, the learning system is paternalistic, harismatic, militaristic, monologue. Improvement efforts can be taken through three steps, namely First, build awareness at all social levels. Second, strengthening the epistemology of education on humanize humans. Third, strengthening the management of social awareness-based education.Keywords: National education problems in Indonesia, national education in the global era, Nassional Education Solutions in the Global Era. AbstrakTujuan dari penelitian ini adalah untuk mengetahui permasalahan pendidikan Nasional di Indonesia dalam konteks global. Metode penelitian ini menggunakan library research. Hasil penelitian menunjukkan bahwa pendidikan nasional mengalami permasalahan diantaranya pertama, kekeliruan filosofis yang mengartikan mutu pendidikan dengan Indeks Prestasi, kedua, lemahnya pemberdayaan tenaga pendidik (pengajar), ketiga manajemen pendidikan bersifat sentralistik, strukturalistik, birokratik, keempat, sistem pembelajaran bersifat paternalistik, harismatik, militeristik, monolog. Upaya perbaikan yang bisa ditempuh melalui tiga langkah yaitu pertama, membangun kesadaran pada semua lapisan masyarakat. kedua, penguatan epistemologi pendidikan untuk memanusiakan manusia, ketiga, penguatan manajemen pendidikan berbasis kesadaran sosial.Kata Kunci: Masalah pendidikan Nasional di Indonesia, pendidikan Nasional di era global, Solusi Pendidikan Nassional di Era Global.